Duration of platelet storage and outcomes of critically ill patients. Issue 3 (March 2017) - Flint, Andrew; Aubron, Cécile; Bailey, Michael; Bellomo, Rinaldo; Pilcher, David; Cheng, Allen C.; Hegarty, Colin; Reade, Michael C.; McQuilten, Zoe
Abstract : BACKGROUND: The storage duration of platelet (PLT) units is limited to 5 to 7 days. This study investigates whether PLT storage duration is associated with patient outcomes in critically ill patients. STUDY DESIGN AND METHODS: This study was a retrospective analysis of critically ill patients admitted to the intensive care unit (ICU) of two hospitals in Australia who received one or more PLT transfusions from 2008 to 2014. Storage duration was approached in several different ways. Outcome variables were hospital mortality and ICU‐acquired infection. Associations between PLT storage duration and outcomes were evaluated using multiple logistic regression and also by Cox regression. RESULTS: Among 2250 patients who received one or more PLT transfusions while in the ICU, the storage duration of PLTs was available for 64% of patients (1430). In‐hospital mortality was 22.1% and ICU infection rate 7.2%. When comparing patients who received PLTs of a maximum storage duration of not more than 3, 4, or 5 days, there were no significant differences in baseline characteristics. After confounders were adjusted for, the storage duration of PLTs was not independently associated with mortality (4 days vs. ≤3 days, odds ratio [OR] 0.88, 95% confidence interval [CI] 0.59‐1.30; 5 days vs. ≤3 days, OR 0.97, 95% CI 0.68‐1.37) or infection (4 days vs. ≤3 days, OR 0.71, 95% CI 0.39‐1.29; 5 days vs. ≤3 days, OR 1.11, 95% CI 0.67‐1.83). Similar results were obtained regardless of how storage duration of PLTs was approached. CONCLUSIONS: In this large observational study in a heterogeneous ICU population, storage duration of PLTs was not associated with an increased risk of mortality or infection.